Some radius problem for certain families of analytic functions - Bolcal, Metin; POLATOĞLU, YAŞAR (TÜBİTAK, 2000)
The aim of this paper is to give bounds of the radius of α-convexity for certain families of analytic functions in the unit disc. The radius of α-convexity is generalization of the radius of convexity and the radius of starlikeness, and introduced by S.S.Miller; P.T.Mocanu and M.O.Reade [3,4]
Keywords: Subordination principle; Carathedory functions; Janowski Starlike functions; Starlike functions of order β; The radius of Starlikeness; The radius of convexity; The radius of α-convexity